2015
DOI: 10.14503/thij-14-4873
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Surgically Placed Impella 5.0 and Central Extracorporeal Membrane Oxygenation Circuit in a Patient with Postcardiotomy Shock

Abstract: 1 Even in the presence of nearly complete cardiopulmonary bypass (CPB) during VA ECMO, some blood will return to the left ventricle (LV). Unlike traditional LV assist device (LVAD) support, VA ECMO pressurizes the systemic arterial circuit without directly unloading the left side of the heart. As a result, the failing LV might not have sufficient contractility to open the aortic valve. This causes progressive LV distention, which impairs myocardial recovery and can lead to pulmonary edema, pulmonary hemorrhage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Other complications of septostomy include needle perforation of the LA and/or pulmonary vein, pericardial effusion, cardiac tamponade, and ventricular fibrillation (32). Furthermore, atrial septostomy may not prevent LV stasis or thrombosis, and may require subsequent repair (6,46). Alkhouli et al [2016] found that the majority (50-75%) of iatrogenic ASDs spontaneously close by 6 to 12 months following simple septostomy (14).…”
Section: Percutaneous Transseptal Ventmentioning
confidence: 99%
See 1 more Smart Citation
“…Other complications of septostomy include needle perforation of the LA and/or pulmonary vein, pericardial effusion, cardiac tamponade, and ventricular fibrillation (32). Furthermore, atrial septostomy may not prevent LV stasis or thrombosis, and may require subsequent repair (6,46). Alkhouli et al [2016] found that the majority (50-75%) of iatrogenic ASDs spontaneously close by 6 to 12 months following simple septostomy (14).…”
Section: Percutaneous Transseptal Ventmentioning
confidence: 99%
“…It is available in three sizes that provide flows of up to 2.5, 3.5 or 5 L/min (53). Several adult and pediatric studies have shown that the use of an Impella device during VA-ECMO improves LVEDD, clinical and radiographic signs of pulmonary edema, and reduces PCWP and PVR (6,7,9,13,46,(54)(55)(56)(57). There is limited evidence that this combination improves survival compared with VA-ECMO alone (56).…”
Section: Vadsmentioning
confidence: 99%
“…This access facilitates the introduction of large self-expanding sheaths into the axillary artery and simplifies the valve mounting maneuver of the balloon-expandable system in the ascending aorta. The chimney approach overcomes access site complications and bleedings from overstretched self-expandable sheaths and is often used for central implanted mechanical circulatory support systems in the case of PAD ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various ventricular unloading techniques have been proposed in this etiology of cardiogenic shock, such as decompression cannula directly inserted through the left ventricular apex, venting via the pulmonary vein or the left atrial appendage, or ventricular decompression with the Impella system (Abiomed, Danvers, Mass) with a surgical transaortic approach or percutaneously with femoral or subclavian artery access. 3 One may consider avoiding the additional surgical trauma to a struggling left ventricle (ie, manipulation associated with positioning the decompressing cannula through the ventricular apex), which could have a certain hypothetical benefit. Moreover, in patients with atrioventricular groove rupture, ventricular access via the mitral prosthesis is not recommended and handling of the friable cardiac mass and the fresh surgical repair could result in persistent massive bleeding.…”
mentioning
confidence: 99%